Street Football, Gender and Muslim Youth in the Netherlands Girls Who Kick Back - Bogert, Kathrine van den (Bloomsbury Studies in Religion, Gender, and Sexuality, 2022)
Based on original ethnographic research in a multicultural neighbourhood in The Hague, this open access book gives detailed insights into the challenges, negotiations and resistances girls with Moroccan-Dutch and Muslim backgrounds face in the world of street football. Kathrine van den Bogert traces the experiences of teenage girls who play football in public playgrounds, as well as in a girls' football competition the girls have set up themselves: Football Girls United. She addresses how race, ethnicity, religion, gender and citizenship are entangled in the access to and construction of the public street football spaces, such as football courts, urban playgrounds and public squares. While Muslim girls in football are often stigmatized and excluded based on their religious and ethnic backgrounds, this book emphasizes their street football practices as critical and creative ways of belonging, both in football and in wider Dutch society. By focussing on a domain largely absent in religion and gender research, namely sport, this book brings forth new perspectives on religious and ethnic diversity in Europe. The football players show that 'Muslim' is not always a relevant identity in their lives, and hence urge us to rethink the categories of analysis that we use, and often take for granted, as feminist and intersectional scholars of gender, religion and Islam. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.